MODEL PENANGGULANGAN TINDAK PIDANA PENCURIAN OLEH BHABINKAMTIBNAS DI WILAYAH HUKUM KEPOLISIAN RESOR BENGKALIS - Andria Familta; Erdianto Effendi; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
The crime level is increasing every year. Especially in the current pandemic situationwhich causes many laid off, control on activities outside the home and the lack of jobs thatmakes the unemployment rate increases. while the necessity of life must be fulfill every day.This kind of situation sometimes making someone taking a short cut by stealing. Criminal actof theft regulated in Criminal code second book about crime against property.Bhabinkamtibnas is part of division police duty. Bhabinkamtibnas is regulated in IndonesianNational Police Chief Regulations No. 3 of the 2015 on the community policing. Handlingminor crimes is classified to problem solving process by Bhabinkamtibnas based onagreement together without any pressure from any side. The purposes of this research is tofind out the Factor that can caused criminal act of theft and to know the specimencountermeasures of the criminal act of theft in the region Police Bengkalis. This research issociological law research because the data obtained directly in place. This research wasconducted in the region Police Bengkalis. The population and sample is all participant thatrelated to research problem. This research uses sources consisting of primary, secondary,and tertiary legal materials. Data collection technique come through by doing someobservation, interview and questionnaire. This research also used qualitative data analysisand produced descriptive data.From the research result, there’s two main thing that can be concluded. First, thefactors caused criminal act divided by two. Internal factors included individual/religion,education and economic and external factors included neighborhood, by chance andcommunity development system. Second, Bhabinkamtibnas has their new crime preventionmodels to press crimes by build some collaboration with footwear business of village ownedby enterprises, doing some guidance and socialization, visiting every house and problemsolving. There’s two advices from the research. First, number of members Bhabinkamtibnasneed to be increased will make the implementation of the task could be optimal. Second,people need to be more open with someone was commited crime. This stigma needs to bebreak because everyone has their own dark path and they have a chance to be better thanbefore.Key word: criminal act of theft, Bhabinkamtibnas, crime prevention models.